2015
DOI: 10.1007/s12648-015-0751-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrinsic degrees of freedom in enhancement of sub-barrier fusion excitation function data and energy-dependent one-dimensional barrier penetration model

Abstract: We have analyzed the role of barrier modification effects (barrier height, barrier position, barrier curvature) introduced due to the energy-dependent Woods-Saxon potential model (EDWSP model) and the coupled channel model on the sub-barrier fusion dynamics of 32;36 16 S þ 90;96 40 Zr reactions. The influence of inelastic surface excitations of colliding pairs and multi-neutron transfer channels is found to be a dominant mode of couplings. The coupling of relative motion of colliding nuclei to these dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In heavy ion fusion dynamics, it has been experimentally observed that the fusion excitation functions for the large number of projectile-target combinations were found to be enhanced over the outcomes made via onedimensional barrier penetration model (1-DBPM) and is one of the most common problems in the heavy-ion interactions. This anomalous behaviour of fusion excitation function introduces the importance of multidimensional tunneling [1][2][3][4][5][6][7][8][9][10][11][12][13]. In literature, it has been well established that the nuclear structure degrees of freedom associated with reaction partners such as low-lying surface vibrations, zero-point motion, neck formation, static nuclear deformation, entrance channel mass asymmetry, rotational states and/or nucleon transfer channels affect the fusion process and played an important role to establish favourable conditions for the synthesis of a particular compound nucleus [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In heavy ion fusion dynamics, it has been experimentally observed that the fusion excitation functions for the large number of projectile-target combinations were found to be enhanced over the outcomes made via onedimensional barrier penetration model (1-DBPM) and is one of the most common problems in the heavy-ion interactions. This anomalous behaviour of fusion excitation function introduces the importance of multidimensional tunneling [1][2][3][4][5][6][7][8][9][10][11][12][13]. In literature, it has been well established that the nuclear structure degrees of freedom associated with reaction partners such as low-lying surface vibrations, zero-point motion, neck formation, static nuclear deformation, entrance channel mass asymmetry, rotational states and/or nucleon transfer channels affect the fusion process and played an important role to establish favourable conditions for the synthesis of a particular compound nucleus [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%